Aspectos agronômicos e econômicos da distribuição de plantas na cultura da soja - Cunha, Vinícius dos Santos (2018)
The way in which plants are distributed modifies intraspecific competition. This competition must be as small as possible, to provide better use of resources in the environment. However, intraspecific competition must be adapted to the production system in which the crop is inserted. The objective of this study was to evaluate the response of soybeans when submitted to different plant distribution scenarios. The study was divided into three experiments with distinct specific objectives: E1) characterize the behavior and the relationship that plant distribution into the row has with soybean grain yield and identify similarities among treatments composed by different cities, irrigation, and cultivars; E2) identify the pattern of grain yield reduction and identifiy if replanting is necessary; E3) evaluate the influence of different row spacings on morphological variables and soybean grain yield. For E1, commercial fields were used in the cities of Cruz Alta, Restinga Seca and São and Gabriel and an experimental area at the Universidade Federal de Santa Maria. In total, 275 samples of a linear meter of soybean were harvested, which were threshes and their mass corrected to 13% of humidity and extrapolated to kg ha-1. In each sample, the spacing between the plants was measured and the following variables were generated: plant population, % of acceptable, double and lack spacings. For E2 and E3, experiments were conducted in the same experimental area of Santa Maria, in the 2014/15 and 2015/16 growing season in randomized block design. The cultivars BMX Tornado RR (undetermined) and FPS Urano RR (determined) of maturity group 6.2 were used in both experiments. E2 consisted of two row spacings (Conventional and Narrow) and four levels of random reduction of the ideal plant population: 0, 25, 50 and 75%. E3 had four row spacings (Conventional, Cross, Twin, and Narrow) implanted in two planting dates (November and December). The plant population presents the highest Pearson’s correlation with grain yield, in all treatments and groups of treatments. The percentage of lack spacings is the only variable that has a negative relationship with grain yield, but with Pearson's linear correlation values lower than |0,50|. The grain yield decreases 1.75% each 10% of reduction in the ideal plant population. When the soybean bushel price is less than US$ 10.50, is unnecessary to replant soybean even plant population decreases 75%. In this case, economic loss is smaller than the costs for replanting. The Narrow row is the only one to reach more grain yield than conventional when planting is done in December and both reach the same result when planting takes place in November. The Twin row has similar grain yield to conventional, but never superior, and Cross row shows the worst performance among all row spacings tested.